Question
upstudy study bank question image url

Three consecutive terms of a geometric series are given in terms of a constant \( x \). \( U_{3}=(x+5), U_{4}=(4 x-1) \) and \( U_{5}=(2 x+3) \). Find the sum to infinity of the series. (Correct to four significant figures). Answer:

Ask by Franklin Page. in Ghana
Feb 15,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The sum to infinity of the series is approximately 6.075.

Solution

We are given three consecutive terms of a geometric series in terms of x:  U₃ = x + 5, U₄ = 4x – 1, U₅ = 2x + 3. Step 1. Find x by using the fact that the ratio between consecutive terms is constant. In a geometric series,  U₄/U₃ = U₅/U₄. So,  (4x – 1)/(x + 5) = (2x + 3)/(4x – 1). Step 2. Cross-multiply to get:  (4x – 1)² = (x + 5)(2x + 3). Expanding both sides:  Left: (4x – 1)² = 16x² – 8x + 1.  Right: (x + 5)(2x + 3) = 2x² + 13x + 15. Set up the equation:  16x² – 8x + 1 = 2x² + 13x + 15. Step 3. Rearranging,  16x² – 8x + 1 – 2x² – 13x – 15 = 0  ⇒ 14x² – 21x – 14 = 0. Divide the entire equation by 7:  2x² – 3x – 2 = 0. Step 4. Solve the quadratic equation using the quadratic formula:  x = [3 ± √(9 + 16)] / (4)  = [3 ± √25] / 4  = [3 ± 5] / 4. Thus, the two solutions are:  x = (3 + 5)/4 = 8/4 = 2  or  x = (3 – 5)/4 = –2/4 = –0.5. Step 5. Determine the appropriate value by finding the common ratio r. For x = 2:  r = U₄/U₃ = (4(2) – 1) / (2 + 5) = (8 – 1)/7 = 7/7 = 1. Since |r| = 1, the series will not converge (and a sum to infinity is defined only when |r| < 1), so we discard this value. For x = –0.5:  r = U₄/U₃ = [4(–0.5) – 1] / (–0.5 + 5) = (–2 – 1) / 4.5 = –3/4.5 = –2/3. Also, U₅/U₄ = [2(–0.5) + 3] / [4(–0.5) – 1] = (–1 + 3) / (–2 – 1) = 2/–3 = –2/3. Since |r| = 2/3 < 1, the series converges. Step 6. Find the sum to infinity S∞. The sum to infinity for a geometric series is:  S∞ = a / (1 – r), where a is the first term. We aren’t directly given the first term, but we know U₃ is the third term, i.e.,  U₃ = a · r². Thus,  a = U₃ / r². For x = –0.5, U₃ = x + 5 = (–0.5) + 5 = 4.5 and r = –2/3, so:  r² = (–2/3)² = 4/9. Then,  a = 4.5 / (4/9) = 4.5 × (9/4) = 40.5/4 = 10.125. Step 7. Now, compute the sum to infinity:  S∞ = a / (1 – r) = 10.125 / (1 – (–2/3)) = 10.125 / (1 + 2/3) = 10.125 / (5/3)     = 10.125 × (3/5) = 30.375/5 = 6.075. Answer (to four significant figures): 6.075.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

To find the sum to infinity of the geometric series given the terms \( U_{3}=(x+5) \), \( U_{4}=(4x-1) \), and \( U_{5}=(2x+3) \), we need to determine the value of \( x \) first, and then the common ratio \( r \) of the series. The general terms of a geometric series have the property that the ratio of successive terms is constant. Therefore, we can set up the equation: \[ \frac{U_{4}}{U_{3}} = \frac{U_{5}}{U_{4}} \] Substituting in our expressions for \( U_{3}, U_{4}, \) and \( U_{5} \): \[ \frac{4x - 1}{x + 5} = \frac{2x + 3}{4x - 1} \] Cross-multiplying gives us: \[ (4x - 1)^2 = (2x + 3)(x + 5) \] Expanding both sides: \[ 16x^2 - 8x + 1 = 2x^2 + 10x + 3x + 15 \] \[ 16x^2 - 8x + 1 = 2x^2 + 13x + 15 \] Rearranging the equation leads to: \[ 16x^2 - 2x^2 - 8x - 13x + 1 - 15 = 0 \] \[ 14x^2 - 21x - 14 = 0 \] Now we can simplify this by dividing all terms by 7: \[ 2x^2 - 3x - 2 = 0 \] Using the quadratic formula \( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \): \[ x = \frac{3 \pm \sqrt{(-3)^2 - 4 \cdot 2 \cdot (-2)}}{2 \cdot 2} \] \[ = \frac{3 \pm \sqrt{9 + 16}}{4} = \frac{3 \pm 5}{4} \] Calculating the two solutions: 1. \( x = \frac{8}{4} = 2 \) 2. \( x = \frac{-2}{4} = -0.5 \) Now, we will substitute \( x = 2 \) back into the original equations: \[ U_{3} = 2 + 5 = 7, \quad U_{4} = 4(2) - 1 = 7, \quad U_{5} = 2(2) + 3 = 7 \] Thus, when \( x = 2 \), all three terms are 7. This confirms that it is a valid geometric series with a common ratio \( r = \frac{U_{4}}{U_{3}} = \frac{7}{7} = 1 \). The sum to infinity of a geometric series is given by the formula: \[ S = \frac{U_1}{1 - r} \] Since \( r = 1 \), we cannot find a finite sum because it diverges. Now let's check \( x = -0.5 \): \[ U_{3} = -0.5 + 5 = 4.5, \quad U_{4} = 4(-0.5) - 1 = -3, \quad U_{5} = 2(-0.5) + 3 = 2 \] The terms do not satisfy the geometric ratio condition, hence we discard it. Since with \( x = 2 \), we have \( r = 1 \), this implies the series diverges leading us to the conclusion: **Therefore, we cannot calculate the sum to infinity as it diverges.**

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy